Vascular Access status at Initiation of Hemodialysis in a Tertiary Care Hospital. - Dilawar, Mubashir; Sabir, omer; Basit, Muhammad Bilal; Farooq, Namra; Ulfat, Majda; Ulfat, Majda; Sami, Mahnum (Pakistan Journal of Kidney Diseases, 2024)
Patients with chronic kidney disease (CKD) 5 are on a slippery slope towards dialysis, however, as is the usual observation, most of the patients’ requiring dialysis do so in an urgent or emergent way using temporary non-tunneled hemodialysis catheter. While temporary vascular access provides a ready access in emergency, nevertheless may be associated with serious complications. In this study we determined the frequency of vascular access at initiation of hemodialysis. Methodology: This was a retrospective analysis of our hemodialysis registry maintained at our dialysis center for the past three years. Total of 124 patients’ complete records were available for analysis. Results: The use of non-tunneled hemodialysis catheter was most common n=101 (81.5%), arteriovenous fistula n=22 (17.7%). Conclusion: Non-tunneled hemodialysis catheter use is highly prevalent in our population initiating hemodialysis.